2017
DOI: 10.1111/ceo.13087
|View full text |Cite
|
Sign up to set email alerts
|

XEN‐45 collagen implant for the treatment of uveitic glaucoma

Abstract: The XEN-45 implant is effective for the treatment of patients with medically uncontrolled uveitic glaucoma. Potentially sight-threatening complications, including bleb-related ocular infection and persistent hypotony, may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 33 publications
2
29
0
4
Order By: Relevance
“…Success was defined by eyes achieving ≥ 20% IOP reduction from baseline on the same or fewer medications without glaucoma-related secondary surgical intervention (SSI) or intention to be converted to another procedure. mITT, modified intent-to-treat; phaco, phacoemulsification with intraocular lens replacement studies with this device, including the US pivotal trial in refractory glaucoma [23], as well as independent, retrospective [14,17,18,[24][25][26] and prospective [12,13,15,16,19,[27][28][29] studies in glaucoma, showing effectiveness at 1 year. Among those, a prospective, open-label study of the implant used alone or in combination with cataract surgery (N = 149 eyes) [16] showed that the mean medicated IOP and mean number of medications decreased from 20.0 (7.1) mmHg and 1.9 (1.3) at baseline to 13.9 (4.3) mmHg (P < 0.01) and 0.5 (0.8) (P < 0.001) at 1 year, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success was defined by eyes achieving ≥ 20% IOP reduction from baseline on the same or fewer medications without glaucoma-related secondary surgical intervention (SSI) or intention to be converted to another procedure. mITT, modified intent-to-treat; phaco, phacoemulsification with intraocular lens replacement studies with this device, including the US pivotal trial in refractory glaucoma [23], as well as independent, retrospective [14,17,18,[24][25][26] and prospective [12,13,15,16,19,[27][28][29] studies in glaucoma, showing effectiveness at 1 year. Among those, a prospective, open-label study of the implant used alone or in combination with cataract surgery (N = 149 eyes) [16] showed that the mean medicated IOP and mean number of medications decreased from 20.0 (7.1) mmHg and 1.9 (1.3) at baseline to 13.9 (4.3) mmHg (P < 0.01) and 0.5 (0.8) (P < 0.001) at 1 year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies demonstrating the IOP-lowering performance and safety of the gelatin implant at 1 year across a spectrum of glaucoma patients have been published [12][13][14][15][16][17]. The present study was designed to evaluate, over 2 years in typical clinical settings, the effectiveness of the gelatin implant as primary surgical intervention in reducing IOP and the number of topical IOP-lowering medications in patients with POAG uncontrolled on topical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on 24 uveitic eyes, Sng et al noted a 60% IOP decline at post-operative month 12 with 83% eyes requiring no further glaucoma surgery. [23] To summarize, the XEN gel stent has shown early favorable data. However, as with other filtering procedures, the true question remains whether or not these blebs will stand the test of time.…”
Section: Intraocular Pressure Controlmentioning
confidence: 98%
“…[28] In uveitic eyes, Sng et al noted a bleb needling rate of 42% (performed at the slit-lamp) within the first 12 months of surgery, while 21% eyes underwent bleb revision in the operating room with dissection of the Tenon's layer within the first 4 months after XEN gel stent implantation. [23] In a study to assess the predictors of needling post-XEN gel stent implantation, Midha et al reported that eyes with lower IOP on day 1 were less likely to require a needling procedure and that a significant association was seen between lower day 1 IOP and lesser number of post-operative needling procedures. [29] The probability of needling was up to 80% in patients having a postoperative day 1 IOP >20 mm Hg while this number decreased to 35% if the day 1 IOP was <10 mm Hg.…”
Section: Bleb Revision/needlingmentioning
confidence: 99%
“…When placed correctly via an ab interno approach, the stent shunts aqueous from the anterior chamber (AC) to the subconjunctival and sub‐Tenon’s spaces. The use of the XEN45 Gel Stent is becoming more widespread, being predominantly used for cases of primary open angle glaucoma but also for the treatment of uveitic and refractory glaucoma …”
mentioning
confidence: 99%